Thrombocytopenia in a Hemodialysis Patient Starting Home Therapy with NxStage System One: Management in a Community Setting - Malvinder S. Parmar (Saudi Journal of Kidney Diseases and Transplantation, 2021)
Platelet dysfunction is common in individuals with advanced chronic kidney disease, and hemodialysis (HD) may cause further activation of platelets, increasing the risk of bleeding and thrombosis. Thrombocytopenia is a potential complication of HD therapy that offen is multifactorial. Both underlying patient-related or specific HD factors may be responsible. We present a case where the patient developed new-onset thrombocytopenia while undergoing training for home HD using NxStage System One. We present a systematic approach in the evaluation and management of this patient that led us to continue with the completion of home HD training and later discharging him on home therapy.